Reliability Analysis of Stone Columns Bearing Capacity - Guechi Yazid; Bordjiba Abdelhak (Modelling in Civil Environmental Engineering, 2021)
Reliability analysis and stone columns techniques are widely used, with an increasing trend, in different geotechnical engineering problems. Design methods of stone columns is still based on deterministic approach, in spite some degree of uncertainties is associated with soil and stone column parameters. In the present work, reliability analysis of bearing capacity of stone columns is examined; using three methods of reliability analysis, First Order Second Moment FOSM, Point Estimate Method PEM, and Monte Carlo simulations MCs. Parametric analysis using all variables involved in stone columns design has been conducted. Distributions of random variables involved in stone columns design are considered either as normal or lognormal. The random variables correlation effect is examined. The study has allowed to evaluate parameter uncertainty effect on reliability index of stone columns, and has permitted to figure out reduced set of parameters that must be considered as random in reliability analysis of stone columns beside sensitivity analysis.